Identification of Avian Influenza Genetic Resistance Gene Marker in Chickens - Susanti, R; Utami, Nur Rahayu; Rahayuningsih, Margareta; Fibriana, Fidia (UI Scholars Hub, 2017)
The Mx gene is a potential candidate as a genetic resistance marker to the avian influenza virus in chickens. The purpose of this study is to identify the potential of Mx gene as a marker of resistance to avian influenza viruses in various breeds of chicken. The study used an exploratory design using three common chicken breeds. The Kampong chicken, the Hy-Line Brown laying hen strain, and the White Leghorn broiler strain were collected from the local farms, and blood samples were drawn from each. The DNA of each sample was amplified by a pair of Mx gene primers (NE-F2/F and NE-R2/R). The polymerase chain reaction (PCR) product of Mx gene fragment was cut using restriction enzymes RsaI to determine the genotype of the Mx gene. The PCR-RFLP analysis in this study showed that 100% of the broilers were GG genotype. In laying hens, 80% were AG genotype, 10% GG genotype, and 10% of the sample was not successfully analyzed. In the Kampong chicken, 68.4% were GG genotype, and 31.6% were AG genotype. The results showed that DNA mutation identification can be applied to determine the genotype chicken against virus. The genotypes of Mx genes in chickens indicates avian influenza virus resistance; whereas, the chicken phenotype does not suggest their level of resistance.